Supercritical water-treated fused silica capillaries in analytical separations: Status review - Karásek, Pavel; Horká, Marie; Šlais, Karel; Planeta, Josef; Roth, Michal (Journal of chromatography. A, 2018)
Near- and supercritical water (SCW) has recently been shown to provide an unusual but effective tool to roughen the inner surface or manipulate the internal diameter of fused silica capillaries for analytical separation methods In this review, the to-date existing variants of instrumental arrangement for etching the fused silica capillaries with SCW are described, the currently accessible morphologies of SCW-etched capillaries are outlined, and both existing and prospective applications of the SCW-etched capillaries in analytical separations are briefly discussed. Relative merits of SCW and other agents to treat the inner surfaces of fused silica capillaries are also mentioned.
Keywords: Supercritical water; Tapered capillary; Water; Capillary electromigration methods; oxid křemičitý; Surface roughness gradient capillary; Fused silica capillary; elektroforéza kapilární; Electrophoresis, Capillary; voda; Silicon Dioxide